ORGANIC PLASTICS: MATERIAL FOR SICK BUILDING SYNDROME CONTROL AND PREVENTION IN BUILDING CONSTRUCTION - Chukwudi, Obi Ifeanyi (International Journal of Research -GRANTHAALAYAH, 2018)
Plastics are organic materials, which consist of synthetic or natural high-molecular compounds (polymers). Due to the large variety of plastic, its different types have different properties, which make it possible to widely use this material in all fields of industry from packaging to the construction industry. The second highest consumer of organic plastics materials after packaging is the construction industry. Thanks to great versatility, cost effectiveness, durability, strength to weight ratio and low maintenance plastics appear to be economically attractive in the construction sector and are used in the manufacturing of wide range of materials in the construction industry. Plastics most times are not easily seen in buildings, but they are widely used in construction and building industry for a vast and wide range of materials, which include insulation, piping, interior design, piping and conduit (rain water, electrical conduits, and sewage pipes, gas distributions and plumbing). Piping and Conduit for instance can consume around 35% of plastic production and are one of the largest consumers of polymers in construction. The purpose of this research is to study plastic as a construction material that can be used to control the formation of Sick building syndrome in buildings, and also as a material that can often be used in the construction industry.